Polyethylene wear analysis: experimental and clinical studies in total hip replacement. - Stilling M (Acta Orthopaedica (Supplement))
Joint replacement is one of the greatest surgical successes in history, and countless attempts have been made in the past to improve the longevity of total hip arthroplasty (THA), including enhancement of implant designs, application of new surface coatings, and development of alternate bearing surfaces. New products have been enthusiastically embraced by surgeons despite lack of clinical support, but not unusually, further experience revealed unexpected drawbacks. Polyethylene (PE) wear has long been recognized as playing a central role in the aetiology of osteolysis and acetabular component failure. However, PE is still the gold standard counter-bearing surface of the femoral head in THA, and despite promising low-wear results of new PE products, there is a continued need for clinical studies to evaluate limitations not exposed by experimental studies. Assessment of low-wear bearing surfaces increases the demand for high precision and high accuracy methods of PE evaluation. Radiostereometric analysis (RSA) is considered gold standard of such measurements, but the method is limited by expense and equipment. Consequently, plain radiographs are still used in many descriptions of clinical wear. New software solutions for plain and stereo radiographs are frequently developed and present a persistent need for method validation and comparison. The first aim of the thesis was to objectivise the clinical importance of hydroxyapatite (HA) coating as a contributor in third-body PE wear, osteolysis, and cup failure, and to focus on the potential of zirconia (Zr) femoral heads as a PE-wear reducing material. The second aim was to explore pit falls and conduct a comparison of three wear measurement methods (EGS-RSA, MB-RSA, and PolyWare), with two-dimensional (2D) and threedimensional (3D) wear estimates. Study I: Twenty-six cementless THA components (HA vs. titanium coating) were evaluated in a randomized patient group with regard for need of cup revision after 15 years' follow-up, and radiographic PE wear and osteolysis after a 12- year follow-up or at end-point revision. HA-coated cups displayed a higher revision rate. There was a positive association between high wear rate and revision, as well as between high osteolysis and revision. Study II: A clinical comparison was performed of PE wear with Zr or cobalt-chrome (CoCr) femoral heads in a young patient group of 69 hips with cementless acetabular shells. At a mean of 5 years, the wear rates were similar and there were no revisions. Study III: Linear PE wear in a long-term followup clinical series of 11 patients was evaluated by use of one, two, or six plain AP radiographs with the same wear measurement method (PolyWare). The number of radiographs used significantly influenced the magnitude of measured linear wear, and wear results with the PolyWare method based on different numbers of radiographs are not comparable. Study IV: Two, new, model-based RSA techniques and a method (PolyWare) for plain radiographs were validated and compared in a phantom hip setup. Methods for 2D wear measurement were more precise (repeatable) and accurate than those for 3D wear measurement. The best concurrent validity was obtained between the MB-RSA and EGS-RSA techniques. PolyWare was the least accurate and precise method, and it demands a twofold larger sample size compared with RSA. Measurement of wear close to liner wear-through severely affects the accuracy of all methods. Study V: As an extension of study III, the Poly- Ware method for plain radiographs using one or two radiographs was compared with EGS-RSA in a clinical series of 12 cementless hips with a minimum 5-year follow-up. Repeatability (precision) for 2D PE wear was similar for PolyWare using only one (the final) radiographs and EGS-RSA ('the gold standard'). The PolyWare method using only the final radiographs is applicable when the expected total 2D wear is above a total of 0.5 mm. From the present clinical studies, it can be concluded that wear in older type non-crosslinked polyethylene liners exceed the defined tolerance of 0.2 mm/year for the development of osteolysis and failure. First-generation hydroxyapatite coating applied to first-generation modular cups resulted in high and early risk of revision, and the clinical performance of recently electrochemically deposited HA coatings should be followed closely. Although no negative effects of Zr femoral heads were observed, an expected clinical wear advantage of Zr femoral heads on PE compared with CoCr femoral heads on PE could not be demonstrated, and long-term follow-ups are needed. Close attention should be paid to the clinical performance of new ceramic products. The methodological studies showed that measurement of PE wear on plain THA radiographs with the PolyWare method should be based on an equal number of radiographs per patient. A good agreement was established between EGS-RSA and PolyWare with use of only the final follow-up plain radiograph for 2D PE wear analysis. The Poly- Ware final follow-up radiograph method is ideal for clinical retrospective research with medium- to long-term follow-ups. It is easy and inexpensive to use, applicable in any hospital, and further alleviates the need for baseline images that are often lost, stored in hard copy, and of varying quality. For assessment of low-wear or short-term clinical follow-up, RSA should be used. Model-based RSA using scanned-surface cup models or computergenerated sphere models are highly accurate and on the level of marker-less RSA for PE wear analysis. Assessment of PE wear near wear-through of the liner is problematic for model-based RSA methods as well as for PolyWare, and it should not be attempted.